2014
DOI: 10.1155/2014/893243
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Myeloid Antigen in Neoplastic Plasma Cells Is Related to Adverse Prognosis in Patients with Multiple Myeloma

Abstract: We evaluated the association between the expression of myeloid antigens on neoplastic plasma cells and patient prognosis. The expression status of CD13, CD19, CD20, CD33, CD38, CD56, and CD117 was analyzed on myeloma cells from 55 newly diagnosed patients, including 36 men (65%), of median age 61 years (range: 38–78). Analyzed clinical characteristics and laboratory parameters were as follows: serum β2-microglobulin, lactate dehydrogenase, calcium, albumin, hemoglobin, serum creatinine concentrations, bone mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
2
19
1
1
Order By: Relevance
“…In the current study, 84% of patients were CD56 positive, which is much higher than the 42% prevalence found by Boshnak and Hashem 14 . Other studies done by Pan et al 11 , Qiu et al 15 and Shim et al 16 reported a prevalence of 71%, 61% and 66%; which is not much lower than that in our study. The presence of CD56 has been related to malignancy in plasma cells, and its downregulation has been shown to be associated with high proliferation and spreading of malignant plasma cells 9 .…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In the current study, 84% of patients were CD56 positive, which is much higher than the 42% prevalence found by Boshnak and Hashem 14 . Other studies done by Pan et al 11 , Qiu et al 15 and Shim et al 16 reported a prevalence of 71%, 61% and 66%; which is not much lower than that in our study. The presence of CD56 has been related to malignancy in plasma cells, and its downregulation has been shown to be associated with high proliferation and spreading of malignant plasma cells 9 .…”
Section: Discussioncontrasting
confidence: 71%
“…CD56 is a homophilic binding glycoprotein implicated in cell-cell adhesion that is involved in attaching plasma cells to the stromal structure of the bone marrow 1 . The prevalence of CD56 positivity in MM varied among studies 11,[14][15][16] . In the current study, 84% of patients were CD56 positive, which is much higher than the 42% prevalence found by Boshnak and Hashem 14 .…”
Section: Discussionmentioning
confidence: 99%
“…). Morphologic subtypes have been shown to be important prognostic factors, with a trend toward immaturity strongly associated with poor prognosis . Mott cells, named after the surgeon F. W. Mott, are plasma cells with spherical inclusion bodies (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of patient with PMMPE is very poor . The morphology of the plasma cells also have a bearing on the prognosis of the patient where plasmablastic differentiation has been shown to be associated with poor prognosis . In this case report, we will discuss the incidence and presentation of PMMPE, morphology of immature plasma cells and mott cells with Russell bodies.…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, this appears to be of significant importance emerging from a study where CD28‐mediated ligation of CD80/CD86 on stromal dendritic cells directly transduced a prosurvival signal to myeloma cell, protecting it against chemotherapy and growth factor withdrawal‐induced death, and induced the dendritic cells to produce the prosurvival cytokine IL‐6 . The aberrant expression of CD28 and myeloid CD33 , the presence of CD98 , and the absence of CD56 and CD117 have been shown to correlate with a poor prognosis of plasma cell‐derived malignancies. The same expression pattern (except slight expression of CD56) was found in UHKT‐944 cells, which is in agreement with rapid progress of the patient's disease.…”
Section: Discussionmentioning
confidence: 99%